Modern Collective Transport. The Impact of Public Policy on the Implementation of the EU Legislative Objectives on the Example of Poland - Jarecki, Stefan Akira (Studia Ecologiae et Bioethicae, 2023)
Urban policy is driven by current trends and ideas. In the 20th century, it was mainly based on modernist views and the most important element of the transport planning policy at that time was the use of the private motor vehicle (car). As a result, transport policies in the 20th century were focused on large-scale road projects, while public transport was marginalized. However, this approach changed drastically at the turn of the 20th and the 21st centuries. Nowadays, the main emphasis is put on environmentally and user-friendly public transport. However, public urban transport often fails to meet the needs of the society. What are the reasons why urban public transport is still not as effective as it should be? The author of this article points in this respect to the poor policy of public bodies responsible for the provision of transport services for the society rather than to the poor quality of the transport law. There are two main areas for improvement - public service planning (defining the service) and cost-effectiveness of providing transport services. The author of the article proposes specific solutions in this regard.